2011
DOI: 10.1375/ajse.35.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Your Voice Counts: Listening to the Voice of High School Students With Autism Spectrum Disorder

Abstract: Supporting students with autism spectrum disorders (ASDs) in inclusive settings presents both opportunities and significant challenges to school communities. This study, which explored the lived experience of nine students with ASD in an inclusive high school in Australia, is based on the belief that by listening to the voices of students, school communities will be in a better position to collaboratively create supportive learning and social environments. The findings of this small-scale study deepen our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 28 publications
5
92
0
1
Order By: Relevance
“…Stakeholders provided no perception that the students' voices were important and there was no evidence of provision to empower them to indicate their needs. Saggers, Hwang, and Mercer (2011) '[recognise] the importance of listening to the voices of students with ASD' (p. 175). While the intention of this research is emancipatory, in part by attempting to provide 'some meaningful practical outcome' (Barnes, 2003, p. 12) regarding transition, an important question that should be considered is how can a shift occur between advocates knowing and claiming what is best for a student to actively including the student in decision-making and allowing them to voice what they see as appropriate for themselves?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders provided no perception that the students' voices were important and there was no evidence of provision to empower them to indicate their needs. Saggers, Hwang, and Mercer (2011) '[recognise] the importance of listening to the voices of students with ASD' (p. 175). While the intention of this research is emancipatory, in part by attempting to provide 'some meaningful practical outcome' (Barnes, 2003, p. 12) regarding transition, an important question that should be considered is how can a shift occur between advocates knowing and claiming what is best for a student to actively including the student in decision-making and allowing them to voice what they see as appropriate for themselves?…”
Section: Discussionmentioning
confidence: 99%
“…Or, more important, interviewing may not be the most appropriate medium for exploring the perceptions of this cohort of students for whom language-processing skills may hinder in-depth responses. However, Saggers et al (2011) successfully used interview techniques in their qualitative study with students with ASD. Other limitations include, but are not limited to, the qualitative research paradigm.…”
Section: Limitations Of the Researchmentioning
confidence: 99%
“…The attitude of students with autism towards socializing with peers was mixed; some preferred to spend time by them-selves, others enjoyed socializing as long as it was in the con-text of a conversation of interest to them, while others found coping with ‗normal' social and academic daily situations stressful (Saggers, Hwang, and Mercer 2011;Sciutto et al 2012).Typical peers were willing to assist students with autism and support communication with them in class but this was less evident during recess. Teachers felt that they were required to facilitate interaction between students with autism and their peers (Soto-Chodiman, Pooley, and Taylor 2012).…”
Section: Teacher and Peers Experiences In Inclusive Settingsmentioning
confidence: 99%
“…Teachers felt that they were required to facilitate interaction between students with autism and their peers (Soto-Chodiman, Pooley, and Taylor 2012). The tendency for students with autism to behave differently from their peers and their difficulties or lack of skills in responding to social situations resulted in students with autism experiencing isolation, teasing and bullying, which were perceived by students, parents and education professionals to be frequently encountered by students with autism (Gray and Donnelly 2013;Hedges et al 2014;Humphrey and Lewis 2008;Humphrey and Symes 2011;Johansson 2014;Saggers, Hwang, and Mercer 2011;Sciutto et al 2012) UNESCO (1994), various international declarations enacted on inclusive education have given the rights to all children to access education in mainstream settings. Research had demonstrated that youngsters with disabilities displayed better social skills and educational success when they found out in the same environment with their normally developing students (Koegel et al2011).…”
Section: Teacher and Peers Experiences In Inclusive Settingsmentioning
confidence: 99%
“…Factors such as developing positive interactions with school staff, providing adaptions to the classroom to reduce noise, creating engaging learning opportunities to facilitate school participation and including the use of students' strengths can all impact on the quality of the school experiences for students on the Autism spectrum (Dillon, Underwood & Freemantle, 2016;Saggers, Hwang & Mercer, 2011 …”
Section: Experiences At School For Students On the Autism Spectrummentioning
confidence: 99%